Health and health care in Israel: an introduction. Issue 10088 (24th June 2017) - Clarfield, A Mark; Manor, Orly; Nun, Gabi Bin; Shvarts, Shifra; Azzam, Zaher S; Afek, Arnon; Basis, Fuad; Israeli, Avi
Summary: Starting well before Independence in 1948, and over the ensuing six decades, Israel has built a robust, relatively efficient public system of health care, resulting in good health statistics throughout the life course. Because of the initiative of people living under the British Mandate for Palestine (1922–48), the development of many of today's health services predated the state's establishment by several decades. An extensive array of high-quality services and technologies is available to all residents, largely free at point of service, via the promulgation of the 1994 National Health Insurance Law. In addition to a strong medical academic culture, well equipped (albeit crowded) hospitals, and a robust primary-care infrastructure, the country has also developed some model national projects such as a programme for community quality indicators, an annual update of the national basket of services, and a strong system of research and education. Challenges include increasing privatisation of what was once largely a public system, and the underfunding in various sectors resulting in, among other challenges, relatively few acute hospital beds. Despite substantial organisational and financial investment, disparities persist based on ethnic origin or religion, other socioeconomic factors, and, regardless of the country's small size, a geographic maldistribution of resources. The Ministry of Health continues to be involved in the ownership and administration of many general hospitals and the direct payment for some health services (eg, geriatric institutional care), activities that distract it from its main task of planning for and supervising the whole health structure. Although the health-care system itself is very well integrated in relation to the country's two main ethnic groups (Israeli Arabs and Israeli Jews), we think that health in its widest sense might help provide a bridge to peace and reconciliation between the country and its neighbours.